Extracorporeal membrane oxygenation (ECMO) assisted mediastinal tumor resection and superior vena cava replacement are safe and feasible. Issue 9 (12th July 2019) - Zhang, Shixin; Tan, Deli; Wu, Wei; He, Bo; Jing, Tao; Tang, Meng; Wu, Tao; Liu, Hongxiang; Zhang, Ming; Zhou, Ni; Tang, Lingfeng; Chen, Qiao; et al.
Abstract : Background: How to maximally improve the drainage of intracranial and upper body venous and to reduce neurological complications during thoracic tumor‐causedsuperior vena cava replacement are still clinical problems to be solved. Methods: We have innovatively used the bilateral jugular vein‐left femoral vein ECMO shunting to perform mediastinal tumor resection and superior vena cava replacement in a 50‐year‐old woman. Results: During the operation, this technique maintained the patient's hemodynamic stability, improved the cerebral oxygen saturation and reduced the cerebral ischemia, hypoxia as well as the neurological complications. Conclusion: It is indicated for patients with superior vena cava replacement who are unable to perform venous bypass (such as innominate vein to right atrial bypass) or venous shunting (such as differential pressure drainage from internal jugular vein to femoral vein).